Innovation in Teacher Preparation: - Using Performance Expectations and Annotated Video to Facilitate Reflection. - Barker, Nan; Plaugher, Randall; Tracz, Susan; DeVoogd, Karen; Plaugher, Joye (Lupa empresarial, 2016)
CalStateTEACH (CST) is a California State University statewide, online, site-supported teacher preparation program that prepares candidates primarily for teaching in elementary school. Teacher candidates engage in academic work online and participate in field experiences at a local school each term. The program promotes innovation, technology integration, and reflection (Mishra, Koehler, & Henrikson, 2011) via the Observation Event (OE) in the clinical practice component of the program. Data collected over three terms in the program is used to monitor candidate progress. The OE is a lesson planning interface that was developed to give teacher candidates greater control over the classroom observation process by determining the lesson focus and pedagogical proficiency levels based on California Teaching Performance Expectations (TPE) (California Commission for Teacher Credentialing [CCTC], 2013). The 13 TPEs are skills a teacher candidate needs to develop by the end of a teachertraining program. These are grouped within the broad range of categories in the Standards for the Teaching Profession: Making Subject Matter Comprehensible to Learners, Assessing Student Learning, Engaging and Supporting Students in Learning, Planning Instruction and Designing Learning Experiences for Students, and Creating and Maintaining Effective Environments for Student Learning (CCTC, 2009). See Figure 1. Candidates begin preparing for the OE by completing a lesson plan and choosing two or three TPEs indicating which aspects of teaching they intend to demonstrate, providing a rationale for that expectation. The elements of the electronic lesson plan include a preconference self-evaluation rationale for proficiency level performance and a reflective video feedback loop for teacher candidates. In the preconference self-evaluation, candidates rank their pedagogical proficiency levels for the TPEs by selecting exploring, applying, proficient, or exemplary, and providing a rationale for the ranking. Faculty mentors provide feedback to the candidate on the lesson plan prior to observing the lesson.